Integration of Jasmonic Acid and Ethylene Into Auxin Signaling in Root Development - Xu, Ping; Zhao, Ping-Xia; Cai, Xiao-Teng; Mao, Jie-Li; Miao, Zi-Qing; Xiang, Cheng-Bin (Frontiers in Plant Science, 2020)
As sessile organisms, plants must adapt their growth and development to changing environment. Root is crucial for plants to absorb water and nutrients as well as a highly dynamic organ of indeterminate growth with new tissues by root stem cells. In order to adapt to fluctuating environment, plants have evolved molecular mechanisms that fine tune root developmental processes. Phytohormones play vital roles in root development. They often relay environmental signals to auxin signaling that ultimately instructs root development programs in order for plants to better adapt to changing surrounding. Therefore, crosstalk among hormones is critical in root development. In this review we will focus on the recent progress that jasmonic acid and ethylene signaling are integrated into auxin in root development of Arabidopsis thaliana and discuss the key roles of transcription factors ERFs and homeodomain proteins in the crosstalk.